The Settlement Morphology along The Musi River - maya fitri oktarini (International Journal of Built Environment and Scientific Research, 2018)
The study examines the morphology of the settements along the Musi riverbank and focuses on the association between the settlements morphology and the characteristic of the river. Musi River consists of three river zones, i.e. upstream, middle, and downstream. The specific morphology that was studied is the distance of the buffer area, the building orientation, and the housing typology that were compared to the physical characteristics of the river and the socio-cultural of the communities. The study data was collected through satellite map and field survey on three settlement sites for each zone, including maps, sketches, photographs, and interviews. The results show the main factors influencing the settlement morphology is the community's dependent on the river. The function of the river for daily life activities influences the distance and the orientation of the settlements. The more the functions of the river for the daily life, the closer and the more oriented their settlements are to the river. Therefore, the river disasters, such as flood and erosion should keep the settlement away from the riverbank. However, the dependence on the river creates the adaptation to on building the settlements that adapt to the natural cycle. It also establishes the morphology of the settlements on the riverbank.